Wellhausen and Kaufmann ancient Israel and its religious history in the works of Julius Wellhausen and Yehezkel Kaufmann - Elrefaei, Aly; Wellhausen, Julius 1844-1918; Kaufmann, Yehezkel 1889-1963; Walter de Gruyter GmbH & Co. KG ([s.l.] Walter De Gruyter GmbH Co.KG, 2016)
This is the first comprehensive study on the subject of the German Biblical scholar and orientalist Julius Wellhausen and the Jewish philosopher and Biblical scholar Yehezkel Kaufmann. It starts with an analysis of their respective works and moves toward a comparison of their views on the history of ancient Israel and its religion. The study shows their similarities, areas of concurrence, as well as the fundamental disagreements between them. Aly Elrefaei,University ofGöttingen, Germany.
"This is the first comprehensive study on the subject of the German biblical scholar and orientalist Julius Wellhausen and the Jewish philosopher and biblical scholar Yehezkel Kaufmann. It starts with an analysis of their respective works and moves toward a comparison of their views on the history of ancient Israel and its religion. The study shows their similarities, areas of concurrence, as well as the fundamental disagreements between them"--
Part II From Religion to History: Yehezkel Kaufmann's Interpretation of Ancient Israel
Description based upon print version of record
Keywords: Wellhausen, Julius -- 1844-1918; Kaufmann, Yehezkel -- 1889-1963; Wellhausen, Julius, 1844-1918; Electronic books; Electronic books; Hochschulschrift